2003
DOI: 10.1017/s0021859603003514
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of maize (Zea mays L.) breeding lines derived from a low nitrogen maize population

Abstract: Eighteen S1 lines of maize (Zea mays L.) derived from a low nitrogen tolerant pool and two inbred lines were evaluated for agronomic performance under moderate N conditions in the southern Guinea savannah of Nigeria. Generally, the breeding lines differed in yield, growth, vertical root-pulling resistance, N-uptake and N-use efficiency. Breeding lines with high vertical root-pulling resistance took up more N and utilized it more efficiently. They also showed better agronomic performance and recorded higher yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
(29 reference statements)
3
20
0
2
Order By: Relevance
“…In this study of principal component use to reduces of original variables into four principal component and information about each variable which support cluster analysis result. These findings were similar to the results founded by Syafii et al (2015) and Kamara et al (2003).In present finding multivariable analysis help to selection of inbred lines for heat stress tolerance breeding: similar to the results reported by Akte ret al, (2009).…”
Section: Discussionsupporting
confidence: 93%
“…In this study of principal component use to reduces of original variables into four principal component and information about each variable which support cluster analysis result. These findings were similar to the results founded by Syafii et al (2015) and Kamara et al (2003).In present finding multivariable analysis help to selection of inbred lines for heat stress tolerance breeding: similar to the results reported by Akte ret al, (2009).…”
Section: Discussionsupporting
confidence: 93%
“…The positive and significant correlations between the components of NUE and GY were similar to the results reported by Heuberger (1998) and Kamara et al (2003). Although the relationship between GY and NUPE at silking under high N was similar to that observed under low N, the stronger correlations of GY with NUPE at harvest under low N suggested that NUPE could play a relatively more important role in determining GY under low N supply Presterl et al 2002).…”
Section: Discussionsupporting
confidence: 88%
“…This might have caused slight change in rankings among the genotypes. Kamara et al (2003) reported genotype Ă— year interaction for maize genotypes evaluated in the Guinea savannas of Nigeria due to slight changes in rankings of the genotypes between the years. The variation among the cowpea genotypes is represented by the mean values (Table 4).…”
Section: Results and Discussion Mean Agronomic Performance Of The Culmentioning
confidence: 99%